Pengaruh Kemudahan Transaksi, Kualitas Produk, Dan Promosi Terhadap Keputusan Pembelian Secara Online (Studi Kasus Pada Konsumen Market Place Shopee Ternate) - Subhan, Subhan; Muvida, Muvida; Hidayanti, Ida E. (Jurnal Ilmu Manajemen, 2022)
Previous studies in the field of consumer online purchasing decisions found that the ease of transaction, product quality and promotion factors determine the level of purchasing decisions. This study aims to determine the effect of ease of transaction, product quality and promotion on consumer purchasing decisions. This research is quantitative research using a survey approach in sampling. The population used in this study is the Shopee market place consumer in the city of Ternate. The technique used in sampling is purposive sampling method. A total of one hundred respondent data meets the criteria that have been set previously. The research instrument was tested first with validity and reliability tests to ensure that the questions were correct in measuring the independent and dependent variables. The analytical method used is multiple linear regression using the SPSS program. The results of this study indicate that the three independent variables studied, namely the ease of transactions, product quality and promotions, are proven to have a positive and significant influence on the purchase decision variable as the dependent variable.